Juvenile redfish (Sebastes spp.) behavior in response to Nordmøre grid systems in the offshore northern shrimp (Pandalus borealis) fishery of Eastern Canada - Araya-Schmidt, Tomas; Bayse, Shannon M.; Winger, Paul D.; Santos, Mark R. (Frontiers in Marine Science, 2022)
A recent rebound of juvenile redfish (Sebastes spp.) in areas where the northern shrimp (Pandalus borealis) bottom trawl fishery in eastern Canada occurs has been challenging the fishing industry to maintain bycatch of this species within acceptable levels. Using self-contained underwater cameras and red lights, this study investigated the behavior of juvenile redfish in response to bycatch reduction devices (BRDs), called Nordmøre grids. Fish behavior was analyzed in grid systems with different bar spacings, including 22- and 19-mm bar spacings. A total of 10.3 h of useable underwater video was collected during commercial fishing conditions, which yielded individual observations of 931 redfish. Generalized linear models (GLMs) and behavioral trees were used to analyze the data. We observed that 52.5% of all redfish passed through the bar spacings and were retained. The duration of the selection process was relatively short ( 1.9 s mean), and 57.8% of redfish reacted to the grids by swimming upwards, forward, or towards with respect to the grids. Behaviors exhibited by redfish and redfish retention were similar for both grids. GLM results suggested that as time in front of the grid increased and redfish had upwards or steady grid reactions, retention was drastically reduced. These were important variables that significantly explained the capture fate of redfish. The behavioral sequence that led to higher escape probability was redfish that approached upwards, had no contact with the grid, and reacted to the grid by continuing to move upwards to finally exit through the escape opening. GLM and behavioral trees gave a comprehensive view of redfish behavior, which is extremely useful for perfecting or developing any BRD to address juvenile redfish bycatch.